The Russian Merchant Afanasy Nikitin's Notes in the 15th Century, “A Journey beyond the Three Seas" - Kerami ÜNAL (Fırat University, 2019)
“A Journey beyond the Three Seas” is a significant literary work written in the 15th century in the form of notes by Afanasy Nikitin between the years 1466-1472 in India. Vasily Mamirov, a priest in Moscow, somehow hit upon the diary and got it recorded in the church inventory. It was discovered by a Russian historian, N. M. Karamzin, in the Troitsko-Sergiyev monastery and published in 1817. In his notes, the Russian merchant recounted the religious beliefs, customs, moral situation and social features of the cultures he encountered and the problems he came across during his journey. The work constitutes in a compendium of the reflections of the author on politics, ethics and art, as well as a bright and clear manifestation of Medieval Russia.